Problematika Pembentukan Peraturan Desa Dalam Perspektif Pengetahuan Hukum Dan Pengawasan - Pratiwi, Dita Ayudia; Gardjalay, Hery Albert; Wattimena, Rovsky Asyer (Bacarita Law Journal, 2025)
This research aims to identify the obstacles faced in the process of forming Village Regulations in Durjela, Wangel and Wokam Villages and then to find out how the role of the Village Government, the Village Consultative Body, and the community in overcoming obstacles in the formation of village regulations. The type of research used in this writing is normative, namely research on the relevant legal norms (laws and regulations), in this research will be used with a descriptive-analytical type of research on the basis that the results obtained from literature studies are then analyzed and discussed using a systematic discussion flow then this research is carried out a literature study (library research), namely collecting related legal materials to obtain objective and accurate information, both from books, laws and the internet. The collection of legal materials is carried out by arranging by subject. The results of the study show that the village government's legal knowledge is lacking in legal knowledge, either due to educational qualifications, lack of seeking information, or lack of legal awareness or lack of supervision in the formation of Village Regulations that are not optimal and effective by the Legal Section of the Aru Islands Regency Government.